Iraq : Staff Report for the 2005 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2005)
Iraq's 2005 Article IV Consultation reports that there has been a marked deterioration in Iraq's human development indicators over the last twenty years. There is relatively little firm data on the balance of payments other than on oil exports, government imports of goods and services, and external reserves. There have been large current account deficits in 2004 and 2005, reflecting high levels of imports related to reconstruction and recovery. The Iraqi government has begun to engage with official creditors in line with the Paris Club agreement.